A methods engineering study on AMI Semiconductors Philippines, Inc - Bacallan, Almer (College of Engineering, 2003)
The group's undertaking to apply methods engineering in AMI-P, a multinational semiconductor company resulted in potential significant improvements in the general layout of, in the individual worksites, and in the systems planning in, the back test department. Furthermore, potential improvements the general situation and conditions of the operators inthe back test were obtained. As requested by the company, the group conducted man-machine studies on the 5 Belgium dedicated machines. This resulted with the conclusion that TR 03 and TR 05 could in fact be operated by just one operator. This translates to at least (assuming minimum wage) P14,560 savings in labor costs monthly. The proposed layout reduce the distance traved by the Belgium products by 18,870 cm or 26.4 percent. These improvements, coupled with the proposed schedule from the systems planning resulted to a reduction of the machine hours on standby by 74.28 percent and resulted to at least P87,353.28 in monthly savings in labor costs. Minor rearrangements in the worksheets to accomodate more materials resulted to P103.22 savings monthly in labor cost, eliminating 657 meter of the distance traveled by operators daily, and reduces by 35.39 hr travel time annually. All these improvements can be implemented almost immediately with practically zero cost. The suggestion to install sensors in the 5 machines to ease the work of the operators will however incur a cost P8,100.0 for the 5 machines. All in all the effort to apply methods engineering to AMI-P back test operations to improve efficiency, and productivity and better working conditions proved to be a success.